The Influence of Dietary n-3 Highly Unsaturated Fatty Acids on Growth, Fatty Acid Profile, Lipid Metabolism, Inflammatory Response, and Intestinal Microflora in F2 Generation Female Yangtze Sturgeon (Acipenser dabryanus) - Jinping Wu; Yuan Liu; Yuqi Wang; Peng Fu; Jiang Luo; Pengcheng Li; Rui Ruan; Junlin Yang; Shijian Xu; Ming Li; Hao Du; Chuang Zhang; et al. (Animals)
DHA and EPA, as indispensable n-3 highly unsaturated fatty acids (HUFAs), exert a fundamental influence on regulating fish growth, lipid metabolism, and overall well-being. However, there is a notable lack of data concerning their effects on the F2 female generation of Yangtze sturgeon. Over a ten-month period, this study assessed the impacts of various dietary concentrations of n-3 HUFAs (0.5%, 1.0%, 1.5%, 2.0%, and 2.4%) on growth, fatty acid composition, lipid metabolism, inflammatory response, and intestinal microbiota in the F2 female generation of Yangtze sturgeon. Seventy-five test fish, with an average body weight of 3.60 ± 0.83 kg, were housed in 15 ponds, with each dietary group being assigned to three ponds. The results indicated that the 1.0%~1.5% n-3 HUFA group was characterized by the highest values of weight gain rate; serum triglyceride levels peaked in the 0.5% n-3 HUFA group. The fatty acid profiles of the fish tissues closely mirrored those of the diets. Specifically, compared to the 1.5% and 2.0% n-3 HUFA groups, the diet containing 2.4% n-3 HUFA down-regulated the mRNA expression of transforming growth factor beta, and, compared to the 0.5% and 1.0% n-3 HUFA groups, the 2.0% n-3 HUFA diet up-regulated the mRNA expression of nuclear factor kappa B. Conversely, compared to the 0.5% n-3 HUFA group, 2.0% n-3 HUFA in the diet up-regulated the gene mRNA expression of fatty acid binding protein 1 and fatty acid synthase. Compared to the 0.5% n-3 HUFA group, 1.0% n-3 HUFA in the diet up-regulated the gene mRNA expression of lipoprotein lipase. The α-diversity indices (ACE, PD_whole tree, Richness, and Chao1) exhibited an upward trend with increasing dietary n-3 HUFA levels, and the 2.4% n-3 HUFA group reached the highest values. At the phylum level, Fusobacteriota, Proteobacteria, Firmicutes, and Bacteroidota were the primary dominant phyla. Cetobacterium was the dominant genus in all groups. Collectively, these findings underscore that moderate dietary supplementation of n-3 HUFA (1.3%) is optimal and does not impair growth. The deposition of fatty acids in muscle and ovarian tissues, as well as the mRNA expression of lipid-metabolism genes, are closely associated with the dietary n-3 HUFA content. High levels of n-3 HUFA did not suppress intestinal α-diversity. These discoveries provide novel insights into the regulation of growth, lipid metabolism, and health in the F2 female generation of Yangtze sturgeon and offer a nutritional strategy for the artificial conservation of this endangered species.